Substance use didorder and bipolar disorder: is cyclothymic temperament endophenotype? - Kesebir, Sermin; Şimşek, Yasemin; Kalyoncu, Ö. Ayhan (Journal of Dependence, 2008)
Objective: The aim of present study was to investigate the relationship of affective temperaments and substance use disorders in bipolar disorder. Testing the relationships with dominant phenomenological features and comorbid conditions would clarify the reliability and validity of temperamental descriptions.Methods: A hundred patients with bipolar I or bipolar II disorder were recruited from consecutive admission and evaluated when euthymic. Temperaments were evaluated with TEMPS-A Turkish version. Information about characteristics of each patient’s illness was obtained by using three main sources; interview with patient (SCID-I), interview with at least one close relative and patient records. We compared the clinical features between patients who have at least one comorbid lifetime substance use disorder and have not.Results: 36 % patients with bipolar disorder also met DSM-IV criteria for at least one comorbid lifetime substance use disorders. Both lifetime and current comorbidity were associated with cyclothymic temperament (p< 0.001 and p=0.037), earlier age at onset of affective symptoms and syndromal bipolar disorder (p=0.045 and p=0.042), switch (p=0.028 and p=0.035), suicid attempt (p=0.045 and p=0.05). Total numbers of episodes and duration of manic episodes were higher (p=0.027 and p=0.034) and longer (p=0.035 and p=0.042) in comorbid group than others. Cyclothymic temperament was associated with positive family history both affective disorder and substance use disorder but there were no differences in family history between bipolar patients with or without substance use disorder.Conclusion: Bipolar spectrum disorders and addiction often co-occur and constitute reciprocal risk factors that the authors believe are best considered under a unitary perspective. These findings suggest that beyond the genetic basis and predisposing role in bipolar disoder, affective temperaments have significant clinical implications and importance. Provacatively, this findings suggest the hypothesis of a common familial-genetic diathesis for a subtype of bipolar disorder and substance abuse.
Keywords: Temperament; bipolar disorder; substance use disorders